2014
DOI: 10.1186/2197-425x-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lung oxidative damage by endogenous superoxide dismutase in sepsis

Abstract: BackgroundThe purpose of this research is to study the relationship between superoxide dismutase (SOD) and lung redox state in an animal model of sepsis.MethodsSepsis was induced in rats by the cecal ligation and perforation model (CLP). After 3, 6, and 12 h, CLP protein content and expression of SOD1, SOD2, and SOD3 were evaluated, and SOD activity was assessed. Oxidative damage was determined by quantifying nitrotyrosine content. Lung localization of SOD3 was performed by immunohistochemistry. The protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Sepsis causes an uneven increase in the relation of SOD and catalase, which exacerbates oxidative stress (Visner et al 1990, Andrades et al 2005, Andrades et al 2011. In this study, all horses showed immunostaining for SOD2 in organs, and horses from the OLG showed increased immunostaining for SOD2, which corroborates the findings of increase of this antioxidant in systemic inflammatory response, especially if caused by sepsis (Constantino et al 2014, Gimenez--Garzo et al 2015. SOD2 present in hoof laminar tissue of horses in this study was observed in different intensities variables between animals, and no difference was observed among experimental groups.…”
Section: Immunostaining For Sodsupporting
confidence: 79%
See 2 more Smart Citations
“…Sepsis causes an uneven increase in the relation of SOD and catalase, which exacerbates oxidative stress (Visner et al 1990, Andrades et al 2005, Andrades et al 2011. In this study, all horses showed immunostaining for SOD2 in organs, and horses from the OLG showed increased immunostaining for SOD2, which corroborates the findings of increase of this antioxidant in systemic inflammatory response, especially if caused by sepsis (Constantino et al 2014, Gimenez--Garzo et al 2015. SOD2 present in hoof laminar tissue of horses in this study was observed in different intensities variables between animals, and no difference was observed among experimental groups.…”
Section: Immunostaining For Sodsupporting
confidence: 79%
“…Oxidative stress has been implicated in the development of tissue injury in several diseases, such as kidney injury as a result of experimental sepsis (Pathak et al 2012), organ failure caused by hemorrhagic shock in kidney, lungs, liver and intestine (Mota-Filipe 1990), and acetaminophen hepatotoxicity (Knight et al 2002). Peroxynitrite, a powerful oxidant agent, can be associated to oxidative lesion by the nitrotyrosine immunostaining in tissues, as observed by Constantino et al (2014) in the lungs of rats submitted to experimental sepsis. Peroxynitrite is formed by the reaction between nitric oxide and superoxide anions ) and promotes endothelial dysfunction, vascular hyporeactivity, primary myocardial disease (Szabó 1996) and inactivation of mitochondrial electron transport, damaging cellular respiration (Radi et al 1994).…”
Section: Immunostaining For Sodmentioning
confidence: 99%
See 1 more Smart Citation
“…antitumoral, antibacterial and antioxidant). [19][20][21][22][23] The main difference between those previously reported ligands (HPClNOL and H 2 BPClNOL) and…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…NT levels were also positively correlated with plasma IL-1, IL-6, TNF-α, oxLDL, and CRP levels. Constantin et al [23] demonstrated that septic animals have increased levels of NT and NO, and that NT plays a prominent role in sepsis. However, it seems that NT levels are more effective in determining the severity of sepsis than are NOx levels, as NT levels were significantly higher in patients with severe sepsis than in patients with mild sepsis.…”
Section: Discussionmentioning
confidence: 99%